Characteristics of Enteroendocrine Cells of White Leghorn Chickens, Gallus gallus, Before and After Hatching - Md. Al amin; Md Salahuddin; Yuriko Imai; Kohzy Hiramatsu (The Journal of Poultry Science, 2023)
The aim of this study was to identify the histological features of chicken enteroendocrine cells before and after hatching. Tissue samples from the duodenum, proximal and distal parts of the jejunum and ileum, cecum and colorectum were collected from the embryos at days 18, 19, 20, and 21 of incubation, and from 3-day-old chicks. The expression of glucagon-like peptide (GLP)-1, somatostatin (SST), and neurotensin (NT) in the enteroendocrine cells was detected using the streptavidin-biotin method, and the colocalization of these peptides was revealed using the double immunofluorescence method. All of assessed peptides were expressed in the enteroendocrine cells at day 18 of incubation. GLP-1-immunoreactive cells were only observed in the jejunum and ileum. The cell numbers gradually increased as incubation progressed. NT-immunoreactive cells were detected in all intestinal parts at all incubation days, and the highest expression was observed in the colorectum of 3-day-old chicks. SST-immunoreactive cells were observed from the duodenum to the ileum, excluding the colorectum. The double immunofluorescence method revealed that GLP-1 and NT colocalized in the same endocrine cells of the jejunum and ileum. The colocalization ratio of GLP-1 with NT was the highest in the distal ileum of 3-day-old chicks. However, neither GLP-1 nor NT colocalized with SST. These results indicate that chicken enteroendocrine cells markedly change their density and colocalization ratios before and after hatching.